Linking Corneal Remodelling to Axial Growth: Induced Peripheral Myopic Defocus and Slow Axial Elongation During 23 Months of Orthokeratology in a 10-Year-Old Girl - Aprilia Elisabet; Ariesanti Tri Handayani; I Gusti Ayu Made Juliari; Surya Ari Wahyudi (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Childhood myopia is the commonest chronic eye disorder of school age, and its harm is carried by axial elongation rather than by blur. Orthokeratology reshapes the cornea overnight into an oblate profile that corrects central vision while imposing myopic defocus on the peripheral retina, but the mechanism is rarely measured in the same child in whom the outcome is measured. Objective: To describe the optical mechanism, corneal remodelling, safety, and axial elongation during 23 months of overnight orthokeratology in a 10-year-old girl with progressive myopia. Case presentation: A paediatric case was followed clinically for 23 months. Serial corneal topography, zonal refractometry, visual acuity, ocular examinations, and optical biometry were assessed. Reshaping was complete by day 26: central axial power fell from 45.60 D to 43.24 D in the right eye and from 45.67 D to 42.78 D in the left, and corneal asphericity reversed from prolate (Q −0.10 and −0.22) to markedly oblate (Q +0.94 and +0.93). Relative peripheral refraction at the 5 mm chord shifted from −0.62 D to −2.12 D in the right eye and from −0.63 D to −2.13 D in the left, corresponding to induced relative peripheral myopic defocus of −1.50 D per eye. Axial length rose by 0.10 mm and 0.11 mm between months 16 and 23, approximately 0.17 and 0.18 mm per year. A transient punctate epitheliopathy at month 11 resolved without interrupting treatment. Conclusion: Overnight orthokeratology produced durable corneal remodelling and peripheral myopic defocus, with slow axial elongation and a reversible minor epithelial event in this child. Baseline axial-length measurement remains essential for treatment monitoring.